Wireless mobile communication and healthcare : 7th International Conference, MobiHealth 2017, Vienna, Austria, November 14-15, 2017, Proceedings /: 7th International Conference, MobiHealth 2017, Vienna, Austria, November 14-15, 2017, Proceedings. (2018) - Unknown
No abstract available